Facteurs prédictifs de décès au cours de la TB pulmonaire chez les PvVIH au CNHU Fann de Dakar - M.L, Harouna Amadou; Doutchi, Mahamadou; Abdoulaye, Ousmane; O., Amadou; M., Abdou Neino; Sani, Kadri; Garba, Abdoul Aziz; Ndour, CT (European Scientific Journal, ESJ, 2018)
Objectives: In sub-Saharan Africa, tuberculosis is the first pulmonary-located opportunistic infection and the leading cause of death among people living with HIV (PLWHA). This paper focuses on studying the predictive factors of death in people co-infected with pulmonary tuberculosis and HIV at the Ibrahima DIOP MAR clinic for infectious and tropical diseases at the CHNU Fann in Dakar. Materials and Methods: This was a retrospective, descriptive, and analytical study conducted from 1st January 1998 to 31st December 2009. It has been of interest to all patients with a successful pulmonary tuberculosis diagnosis and positive HIV status. Epidemiological, clinical, para-clinical, and progressive parameters were studied. Results: A total of 665 cases of tuberculosis/HIV co-infection were observed during the study period, of which 207 deaths or lethality (31.37%) was recorded. The average age of patients was 39±9 years with extremes of 5 and 74 years. The average length of hospitalization was 31.67 ± 20.67 with extremes of 4 and 312 days for surviving patients compared to 19.00 ± 16.42 with extremes of 1 to 90 days for deceased patients. Immunosuppression was significantly associated with death (p=0.001) with a median CD4 of 32.50 elts/mm3. Lethality was significantly elevated in the presence of dyspnea (p= 0, 00014), consciousness disorder (p=10-6 ), motor deficit (p= 0.008), and hemoptysis (p= 0.03). Conclusion: Tuberculosis/HIV co-infection is a common association in Africa. Here, we are talking about a deadly duo. Taking it requires a good knowledge of the factors of poor prognosis and a good integration of the two programs.